Structural basis for genome packaging, retention, and ejection in human cytomegalovirus - Zhihai Li (Nature Portfolio, 2021)
Human cytomegalovirus (HCMV) is the prototypical member of the β-herpesvirinae subfamily and the leading viral cause of congenital infections that can lead to birth defects and it can also cause life-threatening disease in immunocompromised individuals. Here, the authors present the in-situ cryo-EM structures of the symmetry-mismatched portal and the capsid vertex-specific components (CVSCs) of HCMV and discuss the mechanistic implications for genome package, retention and ejection.